Prediction of Soil Bearing Capacity in the Masterplan Area of the Kalimantan Institute of Technology based on GIS - Dyah Wahyu Apriani; Dhea Safitri; Umar Mustofa; Christianto Credidi Septino Khala (U Karst, 2022)
Prediction of bearing capacity and soil type is a requirement for the safety of construction before planning a building construction. Therefore, it is necessary to research the distribution of bearing capacity and conical resistance to determine soil conditions in an area. Based on CPT data, this study mapped cone resistance distribution and soil-bearing capacity distribution in the ITK masterplan area. The analysis was carried out by reviewing the 40 cm pile foundation at 11 m. The analysis was carried out using the Kriging, IDW, and Spline with Barriers methods. The bearing capacity was analyzed using the Trofimankove method. The mapping of the carrying capacity using the three interpolation methods results in a Qall value of around 26,024 â€“ 87,835 tons. The cone resistance mapping results using the three interpolation methods show that the soil consistent in the ITK masterplan area is stiff, very stiff and Hard with a qc value of around 16,0804 â€“ 259,54 kg/cm2. The ITK masterplan area has a type of foundation soil, which is hard. The comparison results obtained from mapping the cone resistance and the carrying capacity of the three interpolation methods used, the value of the range of qc and Qall closest to the sample data used is the IDW methodÂ